Synergistic Effect Initiating Ni1-xCoxMoO4∙xH2O as Electrodes for High-Energy-Density Asymmetric Supercapacitors. (20th February 2017) - Zhang, Xiangdan; Cui, Shizhong; Wang, Nannan; Hou, Hongwei; Chen, Weihua; Mi, Liwei
Abstract: The use of asymmetric supercapacitors (ASCs) with high energy density remains challenging for practical applications. In this study, three-dimensional (3D) hierarchical Ni1− x Cox MoO4 ∙xH2 O microspheres assembled with nanosheets are successfully synthesized using a cation exchange method and used as an ASC electrode material. The optimal synergistic effect of Ni and Co metal ions is obtained by controlling their molar ratio in the aqueous solution. Compared with pure NiMoO4 ∙xH2 O, the presence of Co ion promotes the redox reaction and induces rapid diffusion of electrons. As such, double-metal Ni1−x Cox MoO4 ∙xH2 O exhibits improved electrochemical performance. The developed ASC device of Ni0.67 Co0.33 MoO4 ∙xH2 O//AC shows excellent electrochemical properties and a specific capacitance of 114.6 F g −1 at a current density of 1 A g −1 . The ASC also exhibits outstanding cycling life with 73.28% of the specific capacitance retained after 10000 cycles. Moreover, Ni0.67 Co0.33 MoO4 ∙xH2 O//AC possesses energy density as high as 40.76 Wh kg −1 at a power density of 261.82 W kg −1 . These results indicate that the synergistic effect of Ni–Co can improve the performance of ASCs.